Imaging Approach to Nipple Masses: What a Radiologist Should Know. (15th December 2015) - Omofoye, Toma S.; Scoggins, Marion E.; Dogan, Basak E.
Abstract : The unique milieu of the nipple can give rise to a spectrum of benign and malignant masses. Nipple masses may present a diagnostic challenge to the radiologist due to their location or symptoms, resulting in difficulties in imaging and biopsy access. The purpose of this article is to examine the imaging appearance, workup, differential diagnosis, and management of lesions of the nipple-areolar complex. The nipple-areolar complex can be a blind spot for radiologists, due to poor imaging resolution, confluence of multiple structures, and lack of specific guidelines for image targeting this area. It is important to note that approximately 8% of breast cancers arise in the region of the central mammary ducts near the nipple, and subareolar malignancy may be obscured by normal nipple anatomy.1 This article examines nipple-areolar anatomy, multimodality imaging techniques used for diagnostic evaluation of nipple lesions, and the differential diagnosis of a nipple mass (Table 1 ). In addition, because there are unique diagnostic challenges to percutaneous core needle biopsy of a nipple mass, we discuss the range of biopsy techniques available for sampling these lesions.